The Role of Emotional Intelligence in Leadership and Decision-Making - Gupta, Sakshi; Kaur, Taranpreet (AG Volumes, 2025)
Emotional intelligence (EI) has become essential for building effective leadership and decision-making abilities in today’s dynamic and complex organisational context. The article examines the many studies on the subject of emotional intelligence’s function in decision-making and leadership. This review emphasises how important emotional intelligence (EI) is for improving decision-making and leadership efficacy. Emotionally intelligent leaders, as demonstrated in the Infosys case study, foster positive organizational culture, employee engagement, and improved team performance. Emotional intelligence (EI) enhances leadership qualities including empathy, self-awareness, self-control, and social skills—all of which are essential for resolving conflicts, working with others, and being resilient. Training in EI can significantly improve managerial decision-making, productivity, and business outcomes. The findings emphasize the importance of tailoring interventions to specific EI domains, as understanding emotions enhances decision-making, while perceiving emotions supports interpersonal effectiveness, making EI a critical asset for sustainable organizational success.